Students' Preferences in Visual Consumption on Instagram as the Basis for the University PR-strategy - Kravchenkova, Halyna; Kalashnikova, Alina; Shkrebets, Serhii (Technium Social Sciences Journal, 2021)
In the mediatized society, traditional institutions, specifically high school, are included into economic and communicational competition. They face the necessity to communicate with their publicities by new unfamiliar means, like Instagram, and sometimes fail this challenge because of poor strategy preparation. The present study addresses the issue of incongruity between the visual communication of a higher education organization (Karazin Kharkiv National University as the case) and its young audience’s preferences in visual consumption. To gain a deeper understanding of the real and potential students’ preferences, an online survey was conducted. Data analysis included distributions, means, factor and cluster analysis. As a result, we identified the favorite patterns of photos and their perception, segmented the audience on Instagram by practices of picture evaluation. All this allowed proposing the strategical recommendations for the University PR-strategy, which has already shown its effectiveness for Karazin University and is potentially implementable for any educational institution facing the same challenges